Analysis of Students Ability in Solving HOTS-Based Basic Indonesian - Yuniar Ayu Pratiwi; Rahayu Condro Murti; Aninditya Sri Nugraheni (AL-ISHLAH: Jurnal Pendidikan, 2023)
The study aims to measure and to determine students' thinking skills in solving basic Indonesian questions based on HOTS (Higher Order Thinking Skills). This research uses descriptive qualitative method with content analysis technique. The instrument uses interviews and HOTS-based on multiple choice test questions. The questions given are 6 (six) questions based on indicators of higher-order thinking questions, including the levels of analysis, evaluation and creation. The results of the study show overall that higher order thinking skills are achieved with a percentage of up to 86.66% included in the good/high category. A number of students at the level of C4 (Analysis) of the two questions numbered 1 and 2 reached 73% and 95%, C5 (Evaluation) 53% and 48%, and C6 (Creation) 70% and 95%. Meanwhile, from the results of interviews that have been submitted by students regarding the questions that have been given, it is stated that students are not able to apply reasoning competence easily, interpret and conclude from these questions. It can be concluded that students of UIN Sunan Kalijaga of The Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) class B semester 2 for the 2021/2022 academic year have been qualified in high-level thinking but need to be improved, especially at the C5 level